YODA MAP3K kinase regulates plant immune responses conferring broad‐spectrum disease resistance. Issue 2 (16th February 2018) - Sopeña‐Torres, Sara; Jordá, Lucía; Sánchez‐Rodríguez, Clara; Miedes, Eva; Escudero, Viviana; Swami, Sanjay; López, Gemma; Piślewska‐Bednarek, Mariola; Lassowskat, Ines; Lee, Justin; Gu, Yangnan; Haigis, Sabine; et al.
Summary: Mitogen‐activated protein kinases (MAPKs) cascades play essential roles in plants by transducing developmental cues and environmental signals into cellular responses. Among the latter are microbe‐associated molecular patterns perceived by pattern recognition receptors (PRRs), which trigger immunity. We found that YODA (YDA) – a MAPK kinase kinase regulating several Arabidopsis developmental processes, like stomatal patterning – also modulates immune responses. Resistance to pathogens is compromised in yda alleles, whereas plants expressing the constitutively active YDA (CA‐YDA) protein show broad‐spectrum resistance to fungi, bacteria, and oomycetes with different colonization modes. YDA functions in the same pathway as ERECTA (ER) Receptor‐Like Kinase, regulating both immunity and stomatal patterning. ER‐YDA‐mediated immune responses act in parallel to canonical disease resistance pathways regulated by phytohormones and PRRs. CA‐YDA plants exhibit altered cell‐wall integrity and constitutively express defense‐associated genes, including some encoding putative small secreted peptides and PRRs whose impairment resulted in enhanced susceptibility phenotypes. CA‐YDA plants show strong reprogramming of their phosphoproteome, which contains protein targets distinct from described MAPKs substrates. Our results suggest that, in addition to stomata development, the ER‐YDA pathway regulates an immune surveillance system conferring broad‐spectrum disease resistance that is distinct from the canonical pathways mediated by described PRRs and defense hormones.